2016
DOI: 10.1371/journal.pone.0162548
|View full text |Cite
|
Sign up to set email alerts
|

Subsocial Cockroaches Nauphoeta cinerea Mate Indiscriminately with Kin Despite High Costs of Inbreeding

Abstract: Many animals have evolved strategies to reduce risks of inbreeding and its deleterious effects on the progeny. In social arthropods, such as the eusocial ants and bees, inbreeding avoidance is typically achieved by the dispersal of breeders from their native colony. However studies in presocial insects suggest that kin discrimination during mate choice may be a more common mechanism in socially simpler species with no reproductive division of labour. Here we examined this possibility in the subsocial cockroach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 92 publications
1
9
0
Order By: Relevance
“…The variety of social systems within this group (Lihoreau et al 2012) allows for an exploration of behaviour-population connections within one order, the Blattodea (Inward et al 2007). For example, Blattella germanica, a socially aggregating species, exhibits kin discrimination in mating, but the subsocial species Nauphoeta cinerea does not (Bouchebti et al 2016). This behaviour may then affect population dynamics as inbred-mated N. cinerea females produce 20% less offspring than outbred-mated females do (Bouchebti et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variety of social systems within this group (Lihoreau et al 2012) allows for an exploration of behaviour-population connections within one order, the Blattodea (Inward et al 2007). For example, Blattella germanica, a socially aggregating species, exhibits kin discrimination in mating, but the subsocial species Nauphoeta cinerea does not (Bouchebti et al 2016). This behaviour may then affect population dynamics as inbred-mated N. cinerea females produce 20% less offspring than outbred-mated females do (Bouchebti et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Blattella germanica, a socially aggregating species, exhibits kin discrimination in mating, but the subsocial species Nauphoeta cinerea does not (Bouchebti et al 2016). This behaviour may then affect population dynamics as inbred-mated N. cinerea females produce 20% less offspring than outbred-mated females do (Bouchebti et al 2016). Lihoreau and Rivault (2008) reported that nymphs of B. germanica develop faster in the presence of conspecifics, whereas nymphs of nonaggregating cockroach species did not show benefits from conspecifics.…”
Section: Introductionmentioning
confidence: 99%
“…Family-specific cuticular hydrocarbon (CHC) (Lihoreau & Rivault, 2009) or pheromone patterns (Herzner, Schmitt, Heckel, Schreier, & Strohm, 2006) partly serve as recognition cues on which inbreeding avoidance mechanisms are based on (Lihoreau & Rivault, 2009;Thomas & Simmons, 2011). However, pre-or postcopulatory kin discrimination as inbreeding avoidance mechanisms is not necessarily expressed in all species suffering from inbreeding depression (Bouchebti, Durier, Pasquaretta, Rivault, & Lihoreau, 2016;Edvardsson, Rodriguez-Munoz, & Tregenza, 2008). As alternative or in combination, the costs of inbreeding can be reduced by a polyandrous mating system (Bayoumy, Michaud, & Bain, 2015;Duthie, Bocedi, & Reid, 2016;Tregenza & Wedell, 2002).…”
mentioning
confidence: 99%
“…It is a Blaberidae, ovoviviparous cockroach. N. cinerea is a model species for sexual selection (Bouchebti et al 2016) and correlations between metabolic rate and fitness studies (Schimpf et al 2012). The sample sequenced here was obtained from a Brazilian enterprise that sells N. cinerea specimens for reptile feeding, though the providers could not specify the precise location on which the original specimens were collected.…”
mentioning
confidence: 99%
“…N. cinerea is a model species for sexual selection (Bouchebti et al. 2016 ) and correlations between metabolic rate and fitness studies (Schimpf et al. 2012 ).…”
mentioning
confidence: 99%